Aplikasi Persamaan Rehbock, Kinsvater Ã¢â¬â Carter, Dan Persamaan Umum Pada Bangunan Ukur Segi Empat Skala Laboratorium - Suhardi Suhardi (Department of Physics Education, Universitas Mataram, 2019)
The rectangular sharp-crested weir often finds in irrigation open channels. The function of the rectangular sharp-crested weir measures and divides the water flow to be distributed to agricultural lands. The Rehbock equation, the Kinsvater-Carter equation, and the General equation are used to approach the discharge. On a laboratory scale, the measurement of the discharge using a small rectangular sharp-crested weir was used for experiments and simulations. Because of using The Rehbock equation, The Kinsvater-Carter equation, and The General equation for a field discharge measurements, it is necessary to research to find out the accuracy of the Rehbock Equation, the Kinsvater-Carter equation and the General equation in the laboratory scale. The research data included the dimensions of rectangular weirs, the height of the water on the rectangular sharp-crested weir, the width of the channel on the hydraulic bench and the actual discharge. Data collection of the height of water on the rectangular sharp-crested weir and the actual discharge was carried out 5 times the measurements with different discharges. These data were analyzed using the Rehbock equation, the Kinsvater-Carter equation, and the General equation. The discharge of the analysis results was compared with the actual discharge to find out the value of the calibration coefficient. The experimental results show that the Kinsvater-Carter equation and General equation can be applied for discharge measurements on the laboratory scale. The calibration coefficient for the Kinsvater-charter equation was 0.89 and the calibration coefficient for the general equation was 0.94.